2009 IEEE International Symposium on Circuits and Systems 2009
DOI: 10.1109/iscas.2009.5118230
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of structural adders in fixed coefficient transposed direct form FIR filters

Abstract: Over the last two decades, fixed coefficient FIR filters were generally optimized by minimizing the number of adders required to implement the multiplier block in the transposed direct form filter structure. In this paper, an optimization method for the structural adders in the transposed tapped delay line is proposed. Although additional registers are required, an optimal trade-off can be made such that the overall combinational logic is reduced. For a majority of taps, the delay through the structural adder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Nevertheless, when the transposed structure is used in both, the model subfilter and its complementary pair, a huge amount of extra delay elements needs to be aggregated. It has been shown that delays have a hardware cost similar to adders [15]. Thus, the use of transposed structures leads to an inefficient implementation in terms of usage of hardware resources, which is translated into a high demand of chip area.…”
Section: The Problemmentioning
confidence: 99%
“…Nevertheless, when the transposed structure is used in both, the model subfilter and its complementary pair, a huge amount of extra delay elements needs to be aggregated. It has been shown that delays have a hardware cost similar to adders [15]. Thus, the use of transposed structures leads to an inefficient implementation in terms of usage of hardware resources, which is translated into a high demand of chip area.…”
Section: The Problemmentioning
confidence: 99%
“…However, more adders are required compared to multiplier blocks designed by CPAs for word lengths of coefficients larger than 9 bits [12]. Moreover, the use of the redundant carry-save representation The area optimization of SAs in transposed form FIR filters was first investigated by Faust and Chang in [13]. To the best of our knowledge, this is another pioneering work where pipelining of structural adders is considered.…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that half adders could be completely removed by selecting a suitable sign of each partial result. In [17], a technique for reducing the number of full adder cells for the structural adders, the adders between the delay elements in Fig. 1, was proposed.…”
Section: Introductionmentioning
confidence: 99%